Performance Assessment of the Acute Physiology and Chronic Health Evaluation IV Scoring System in Outcome of Patients fallowing Acute Poisoning - Khodabandeh, Farideh; Shadnia, Shahin; Pormatine, Matien (Novelty in Biomedicine, 2018)
Background: The present study aims to assess the ability of the acute physiology, chronic health evaluation IV (APACHE IV) scoring system to predict in-hospital mortality of intensive care unit (ICU) patients with acute poisoning. Materials and Methods: Using data from 622 consecutive ICU admitted poisoned patients, Loghman-e-Hakim Hospital, Tehran, during May 2015-April 2016. Various statistical tools used to assess the correlation, significance, and predictability. Results: Overall APACHE IV scoring system was statistically significant (P=.001). Death rate prediction, increased from 79.4% to 86.8 % by model, with SMR =0.83%. A meaningful association between APACHE-IV score and the risk of mortality with good discrimination and, calibration (p value of 0.978) was evident. Conclusion: The present study demonstrates that the APACHE IV system performs acceptably in our patients with acute poisoning and can be utilized as a performance assessment tool in poisoning centers.